(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Twenty eight species belonging to twenty six genera and two unidentifiable genera are reported and figured from twelve isolated localities of the Dingjianzhai Formation in the Baoshan Block, western Yunnan, China. Four new species, Bandoproductus qigshuigouensis n. sp., Callytharrella dongshanpoensis n. sp., Trigonotreta semicircularis n. sp. and Punctocyrtella? yunnanensis n. sp., are described. Based on the stratigraphic distribution of the brachiopod species throughout the Dingjiazhai Formation, three assemblages are recognizable, which in ascending order are: Bandoproductus qingshuigouensis-Marginifera semigratiosa Assemblage (Asselian age), Punctocyrtella australis-Punctospirifer afghanus Assemblage (most likely latest Asselian-Early Sakmarian) and Callytharrella dongshanpoensis Assemblage (Late Sakmarian-Artinskian). The Early Permian Dingjiazhai brachiopod fauna as a whole demonstrates strong generic and specific links with those of Gondwanan and Perigondwanan faunas, but also demonstrates limited but significant links with those of the eastern Palaeotethyan faunas.